2015
DOI: 10.1097/md.0000000000001986
|View full text |Cite
|
Sign up to set email alerts
|

Classification and Morphological Parameters of the Scapular Spine

Abstract: Incidence of scapular spine (SS) fractures as a result of complications of reverse total shoulder arthroplasty is relatively high leading to inferior clinical outcomes and an increased risk of revision and dislocation. Fractures of SS because of trauma, including the acromion, constitute 6% to 23% of scapula fractures. The purpose of this study was to classify the SS and present specific geometrical parameters according to osteologic features. A total of 319 intact dry scapulae were collected and classified ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
2
5
0
Order By: Relevance
“…Other studies performing measurements mostly in Levy zone I on anteroposterior (AP) radiographs corroborated these findings by Werthel et al 8,16,20 . Measuring acromial midsubstance thickness more closely aligns with the risks reported by biomechanical studies 17,34-36 . Thus, the acromial midsubstance thickness on scapular Y-view may provide prognostic value, whereas the thickness of the anteromedial acromion (Levy zone I) has lesser relevance.…”
Section: Patient Risk Factorssupporting
confidence: 73%
See 1 more Smart Citation
“…Other studies performing measurements mostly in Levy zone I on anteroposterior (AP) radiographs corroborated these findings by Werthel et al 8,16,20 . Measuring acromial midsubstance thickness more closely aligns with the risks reported by biomechanical studies 17,34-36 . Thus, the acromial midsubstance thickness on scapular Y-view may provide prognostic value, whereas the thickness of the anteromedial acromion (Levy zone I) has lesser relevance.…”
Section: Patient Risk Factorssupporting
confidence: 73%
“…There is substantial heterogeneity in scapular morphology, which requires consideration during baseplate fixation and screw placement. Two in vitro scapula morphology studies, both of which measured the SS and acromion thicknesses in various planes, found that fusiform and s-shaped SS may be at a greater risk of fracture based on having multiple points of a significantly thinner acromion and SS 34,35 (Fig. 2).…”
Section: Patient Risk Factorsmentioning
confidence: 99%
“…Based on morphological classifications, Hua Jun Wang states that Type 1-Fusiform shape (47.17%) and Type 5-Horizontal S-shape (19.18%) were the most common, followed Type 4-Wooden club shape (13.21%) and Type 3-Thick rod shape (12.58%). Type 2-Slender -rod shape (7.86%) was the least common [9]. In our study the Type 5-S Shape (0%) was the least common, commonest being type 1-fusiform(35%), followed by type IV (28%) and type III(21%).…”
Section: Resultssupporting
confidence: 44%
“…Four weeks after surgery, the patient was brought to the emergency department and admitted overnight after a fall on ice at the train station. Radiographs ( figure 1A, B ) and a CT scan ( figure 1C ) confirmed a displaced lateral SS fracture at the base of acromion 1 in a type 1 fusiform shaped SS 2 as seen on the radiograph ( figure 1B ) and as confirmed on CT scan.…”
Section: Case Presentationmentioning
confidence: 66%